Structure of Parascaris equorum (Goeze, 1782) population in horses in different season in East Caucasus - R. I. Hasanova (Российский паразитологический журнал, 2016)
The seasonal dynamics of Parascaris equorum infection in horses in terms of the Chechen Republic is studied. P. equorum infestation in young horses varies slightly during the year. In the autumn infestation in young horses increases to 48,1 %.